Career paths of Ministry of Finance advisers - Filippo Silano (University of Hamburg, Institute of Law and Economics (ILE), 2023)
Ministry of Finance advisers play a crucial role in managing public finance matters, acting as a bridge between bureaucratic and political realms. This article aims to identify the essential skills and experiences that advisers must possess and how these professional qualities relate to their appointments. Collating a unique longitudinal dataset from selected OECD countries, this study employs sequence analysis and network science to identify common career paths and a transnational network encompassing governmental bodies, standard-setters, and academia. The research also uncovers significant variations in professional trajectories across and within countries, indicating that diverse advisory traditions and ministerial strategies require specific skills and experiences. This article sheds light on a relatively unexplored aspect of public finance policymaking by focusing on these often overlooked actors. Inductively, it enhances the understanding of ministerial advisers by highlighting how individual characteristics play a role in their appointment.
Keywords: P16; H11; H30; H39; H60; H83; 330; government; ministerial advisers; careers; sequence analysis; optimal matching; social network analysis; economic sociology; comparative politics